Tác động của ứng dụng Marketing số trả phí đến sự lựa chọn của khách hàng tại khách sạn 5 sao ở Huế - Tống Viết Bảo , Hoàng; Phạm Xuân, Hùng; Lê Thị Phương, Thanh; Lê Thị Phương, Thảo; Hoàng Việt Hạnh, Nguyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
In the context of the rapid shift in tourism behavior toward digital environments, clarifying the role of Paid Digital Marketing in hotel choice has both theoretical and practical significance. This study examines the impact of Paid Digital Marketing in the five-star hotel segment of Hue, Vietnam, and conceptualizes Paid Digital Marketing as a higher-order construct consisting of three components: search engine marketing, display advertising, and social media marketing. The study draws on the logic of the Stimulus–Organism–Response (S-O-R) framework to interpret the mechanism through which Paid Digital Marketing influences customers’ hotel choice. Survey data from 651 tourists were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a reflective–formative higher-order construct. The results indicate that all three components significantly contribute to Paid Digital Marketing, with social media marketing exerting the strongest effect. Furthermore, Paid Digital Marketing has a significant positive impact on hotel choice (R² = 0.703). This study contributes to a better understanding of the structural composition of Paid Digital Marketing in the context of upscale hotels in an emerging market. The findings also suggest that five-star hotels in Hue should prioritize social media marketing while optimizing search engine marketing and display advertising to enhance the effectiveness of online customer acquisition.